A comprehensive review on eutectic phase change materials: Development, thermophysical properties, thermal stability, reliability, and applications - Abhishek Anand; Muhamad Mansor; Kamal Sharma; Amritanshu Shukla; Atul Sharma; Md Irfanul Haque Siddiqui; Kishor Kumar Sadasivuni; Neeraj Priyadarshi; Bhekisipho Twala (Alexandria Engineering Journal)
Phase change materials (PCMs) are important constituents for the storage of thermal energy available from the sun. It acts as a bridge between energy demand and supply while reducing the mismatch. Organic and inorganic constituents have been used for a long time for thermal energy storage applications. In recent years, the focus has been shifted to eutectics. A eutectic is a minimum melting substance of two or more constituents. It has the advantage of having a sharp melting temperature and possessing high volumetric heat storage density. The eutectics possess a wide range of temperatures and have the properties of all of their constituents. At present organic-organic, organic-inorganic, and organic-inorganic eutectics are widely studied. In the present paper, various eutectic PCMs for low and medium temperature ranges have been analyzed. Their thermophysical properties and thermal stability and reliability concerning thermal cycling have been thoroughly discussed. The melting temperature lies in the range of −23.50 °C to 80 °C and the latent heat of fusion can be as high as 280 kJ/kg. Thermal cycle tests of up to 30000 have been conducted by various research groups, but at least 300 melt/freeze cycles are recommended so that they can be stable for a year of application. The organic eutectic PCMs are found stable in terms of deviation in melting temperature with the maximum deviation in latent heat of fusion observed was ± 20 %. The inorganic eutectic PCMs are somewhat unstable having a large deviation in melting temperature and latent heat of fusion. The low thermal conductivity of organic eutectics can be eliminated with suitable nanoparticle additives. The leakage issue can be eliminated by providing shape stabilization to the PCMs. These PCMs are suitable for various photovoltaic/thermal, buildings, textiles, solar water heating, solar air heaters, and heat recovery systems applications.